Optional Protection People’s Social Life - Kasmauskas, Saulius (Ekonomika, 2001)
There is an article about optional protection people’s social life in this paragraph. The optionalism is like a presumption with safeguarding for people earlier, in nowadays and in a further future. The idea of optionalism consists of the main part of human law. This is for safeguarding of community and their purposes. The call pay is criticized and necessity of law exception is accentuated too. It is very important thing for Christian education. The others restrictions are for licenciat for development of economical life, so it is warning about vital activities poor people which can’t be in full value. Acknowledge the receipt of optionalists ideas forming for Europe Union and its indication. The every person irrespective of their abilities and level of development should have possibility to take part in ruling public goodness creation and this is the main presumption in general public. The human like a social creature has his personal property what can safeguarding of peace and security not only his personal goodness. Better life and work, to use every goodness for giving and social common welfare for other people either.